Pollen sensitivity to ultraviolet-B (UV-B) suggests floral structure evolution in alpine plants - Zhang, Chan (Nature Publishing Group, 2014)
Various biotic and abiotic factors are known to exert selection pressures on floral traits, but the influence of ultraviolet-B (UV-B) light on the evolution of flower structure remains relatively unexplored. We have examined the effectiveness of flower structure in blocking radiation and the effects of UV-B on pollen viability in 42 species of alpine plants in the Hengduan Mountains, China. Floral forms were categorized as either protecting or exposing pollen grains to UV-B. The floral materials of plants with exposed and protected pollen grains were able to block UV-B at similar levels. Exposure to UV-B radiation in vitro resulted in a significantly greater loss of viability in pollen from plant species with protective floral structures. The pronounced sensitivity of protected pollen to UV-B radiation was associated with the type of flower structure. These findings demonstrate that UV-B plays an important role in the evolution of protective floral forms in alpine plants.